An Empirical Examination of IPO Underpricing Between High-technology and Non-high-technology Firms in Taiwan. (April 2019) - Gao, Simon; Hou, Tony Chieh-Tse
This study investigates the determinants of initial public offering (IPO) underpricing by focusing on variables relating to information asymmetry, investor sentiment and corporate governance and examines whether the determinants of IPO underpricing in high-technology and non-high-technology IPOs differ. With data from Taiwan for 2009–2011, this study finds that overallotment is negatively related to underpricing, whereas market momentum, first-day trading volume and managers' ownership retention rates are positively related to underpricing, particularly for high-technology IPOs. Our results support the signalling hypothesis in high-technology IPOs. JEL Classification: G12, G14, G24, G32